LAMA PENGERINGAN TERHADAP AKTIVITAS ANTIOKSIDAN DAN MUTU TEH HERBAL DAUN KETEPENG CINA (Cassia alata L.) - Yamin, Muhammad; Ayu, Dewi Furtuna; Hamzah, Faizah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study ware to obtain the effect of drying time of antioxidant activity and to obtain quality of herbal tea ketepeng cina leaf (Cassia alata L.).  This study used a completely randomized design with 5 treatments and 3 replications.  The treatments used were drying time P1 (drying 110 minutes), P2 (130 minutes), P3 (150 minutes), P4 (170 minutes) and P5 (190 minutes).  Data were analyzed statistically using ANOVA and DNMRT at 5% level.  The results showed that the drying time significantly affected yield, moisture content, ash, crude fiber, antioxidant activity, and sensory assessment (descriptive and hedonic) but didn’t significantly affected on ash content.  The treatment chosen from the results of this research was drying time P2(130 minutes).  Treatment of P2 has a yield 49.70%, water content 7.17%, ash of 1.24%, crude fiber 15.48%, and antioxidant activity (IC50) 60,18 ppm.  The test of sensory descriptive and hedonic of herbal tea ketepeng cina leaf from treatment P2 showed that the color of brewed tea was yellow, the aroma of brewed tea was scented ketepeng cina leaf, and taste steeping tea was astringent.  The overall assessment of herbal tea ketepeng cina leaf was rather preferred by the panelists. Keywords: herbal tea, ketepeng cina, antioxidant activity, and drying time.